Adapting to change: Undergraduate dental students' learning experiences and perceived enablers and barriers during the post-COVID-19 transition from online to onsite education - Lin, Galvin Sim Siang; Cockburn, Jessica Grace; Pallath, Vinod (Islamic International Medical College, Riphah International University, 2026)
Objective: The present study aimed to explore final-year undergraduate dental students' learning experiences and their perceived enablers and barriers during the post-COVID-19 transitional phase from online to onsite education. Study Design: A qualitative case study design using focus group discussions was employed in accordance with the Consolidated Guidelines for Reporting Qualitative Research (COREQ) checklist. Place and Duration of Study: Faculty of Dentistry, Asian Institute of Medicine, Science and Technology (AIMST) University, from April 2022 to June 2023. Materials and Methods: Homogeneous convenience sampling was used to identify final-year undergraduate dental students currently enrolled at AIMST University Malaysia. Eighteen dental students were recruited and randomly assigned to three groups. They were invited for an online discussion through the recorded Zoom platform. The focus group discussions were audio-recorded and transcribed verbatim. Thematic analysis was performed using an inductive approach. Results: Three major themes were discovered: (1) Perception of learning facilitating experiences, (2) Perceptions of learning impeding experiences, and (3) Factors influencing learning during transition. The first major theme is divided into five sub-themes: clinical hands-on, treating 'real' patients, knowledge acquisition and understanding, teaching quality, and social interaction. Meanwhile, two sub-themes emerged from the second major theme: expectation and challenging schedule. Finally, the third major theme is divided into six sub-themes: adaptability, confidence and readiness; changes in availability of support; lifestyle; communication; and technical. Conclusion: Undergraduate final-year dental students reported both facilitating and impeding learning experiences during the COVID-19 transitional period. Dental educators should tailor the current dental education and pedagogical structures to suit the needs and demands of dental students when the country has fully entered the endemic phase.